Inside Cover: A Synergistic Capture Strategy for Enhanced Detection and Elimination of Bacteria (Angew. Chem. Int. Ed. 23/2014). Issue 23 (15th April 2014) - Li, Yong‐Qiang; Zhu, Bowen; Li, Yuangang; Leow, Wan Ru; Goh, Rubayn; Ma, Bing; Fong, Eileen; Tang, Mark; Chen, Xiaodong
<x xml:space="preserve">Abstract</x> Efficient bacterial capture was achieved through a method based on the synergistic effect of surface nanotopography and surface chemistry on bacterial attachment. In their Communication on page 5837 ff., X. Chen and co‐workers show that packed silicon nanowires functionalized with bacteria‐binding molecules show enhanced capture efficiency compared to surface‐modified flat silicon and enable highly sensitive detection and efficient elimination of bacterial pathogens.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>